Chapter 2 Galen in Late Antique Medical Handbooks - Bouras-Vallianatos, Petros (Brill, 2019)
This chapter explores the use and adaptation of the Galenic corpus in the hands of late antique medical compilers. It is divided into two main sections dealing with Greek and Latin authors respectively.